FAKTOR - FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR DI BEI - WENNY WENNY; YOHANES YOHANES (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to empirical test data regarding the factors that influence the tax aggressiveness of the manufacturing companies on Indonesia Stock Exchange (IDX). These factors are the variables of leverage, liquidity, capital intensity, independent commissioner, inventory intensity and profitability. The population used in this study is a manufacturing companies which are listed in the Indonesian stock exchange from 2017 to 2019. Determination of the sample was made by applying purposive sampling method and there are 82 companies that have met the sample criteria. The hypothesis that researchers use for this research is multiple regression analysis. The results of this research show that the profitability has an effect on tax aggressiveness. However the leverage, liquidity, capital intensity, independent commissioner and inventory intensity have no effect on tax aggressiveness. The results of this study are expected to be used as information and knowledge in conducting research also to provide an overview to companies in carrying out their operational activities related to behavioral control on tax aggressiveness and for government to know company implement tax aggressiveness. The diference in this study from previous research is adding the variables of Inventory Intensity, Profitability